THE DESIGN OF A STOCK TAKING INVENTORY APPLICATION BASED ON ANDROID - Reni Haerani; Pegie Desianasari (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2022)
Abstract.  The stocktaking activities at the company take a relatively long time depending on the number of goods and assets owned. As a result, the company can only carry out stock taking at the end of the day or in a non-peak season. This condition resulted in the company’s being disorganized in doing stocktaking. This study aims to create an application that can facilitate the management of stocktaking inventory of goods. The system development method uses the SDLC (System Development Life Cycle) model. Which has the stages of planning, system analysis, system design, system implementation, system testing and system maintenance. Application improvement starts from system preparation to detailed system design terms, including database design, input output design, and Android-based technology. The information system is built using Android Studio using the Java programming language. This study resulted in a stock-taking application for inventory that stores information about stock taking inventory by displaying features of stock ownership data, inventory items, updating item data, and stocktaking inventory reports. It is hoped that PT. Barata Indonesia (Persero)Turbine Component Division will quickly, effectively, and efficiently in data processing stocktaking inventory of existing goods and compiling reports per period systematically. Keywords: Android; Inventory; Stocktaking Abstrak- Aktivitas stock opname dalam perusahaan memakan waktu yang relatif lama bergantung menurut banyaknya barang dan aset yang dimiliki, sebagai akibatnya perusahaan hanya bisa melaksanakan stock opname waktu  akhir atau dalam keadaan tidak ramai (non-peak season).  Kondisi ini mengakibatkan perusahaan tidak tertib dalam mengerjakan stock opname. Penelitian ini bertujuan menciptakan aplikasi yang bisa memudahkan manajemen stock opname persediaan barang. Metode pengembangan sistem menggunakan model SDLC (System Development Life Cyle) dimana mempunyai tahapan-tahapan Perencanaan, Analisis Sistem, Perancangan Sistem, Implementasi Sistem, Pengujian sistem dan Perawatan sistem. Perbaikan aplikasi dimulai dari persiapan sistem sampai termin  desain sistem yang rinci, meliputi rancangan database,  input output, sampai teknologi berbasis android. Sistem informasi dibangun menggunakan  android studio menggunakan bahasa pemrograman java. Penelitian ini menghasilkan sebuah aplikasi stock opname persediaan barang yang menaruh informasi tentang stock opname persediaan barang  dengan menampilkan fitur data stock opname, persediaan barang, update data barang dan report stock opname persediaan barang. Diharapkan bisa  dipakai  pihak PT. Barata Indonesia (Persero) Divisi Komponen Turbin secara cepat, efektif  dan efisien  pada pengolahan data stock opname  persediaan barang yang terdapat dan menyusun laporan per periode secara sistematis.Kata Kunci : Android; Persediaan Barang; Stock Opname